STUDI PENGELOLAAN TENANT MALL OUTDOOR FOOD AND BEVERAGE - Putra Adhitama; Sylvie Wirawati (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
The Breeze BSD is one of the outdoor food and beverage malls managed by The Breeze BSD manager under PT SinarMas which was inaugurated in 2013. Qualitative Data: Physical condition Management of tenants and outdoor food and beverage mall facilities The Breeze Quantitative Data: Quantitative data is data obtained from the manager and the results of the respondent's questionnaire. The author received field facts obtained from several visitors to The Breeze related to the existing facilities. The visitors said that the facilities were in the form of restaurants, elevators, hand washing areas, sports & entertainment areas, etc. In addition, there are also facilities that lack facilities that need to be added. For example, adding toilet points, motorbike parking slots, hangout areas, live music areas, ATM centers. The impact of the COVID-19 pandemic caused several tenants to close and reduce employees due to not being able to pay employees and pay rent so that The Breeze's income decreased quite significantly. Based on the field facts above, the author wants to do more in-depth research on Knowing management's efforts in managing tenants and facilities. Keywords: food and beverage; outdoor; Management; Tenant mall Abstrak The Breeze BSD merupakan salah satu mall outdoor food and beverage yang dikelola oleh pengelola The Breeze BSD dibawahi oleh PT SinarMas diresmikan pada tahun 2013. Data Kualitatif : Kondisi fisik Pengelolaan tenant dan fasilitas mall outdoor food and beverage The Breeze Data Kuantitatif : Data kuantitatif merupakan data yang didapat dari pengelola dan hasil kuesioner responden.Penulis mendapat fakta lapang yang diperoleh dari beberapa pengunjung The Breeze terkait dengan fasilitas yang ada. Pengunjung-pengunjung tersebut mengatakan bahwa fasilitas berupa restoran, lift, temapt cuci tangan, area sport & entertainment dll. Selain itu, terdapat juga fasilitas yang kurang fasilitas yang perlu ditambah. Misalnya, penambahan titik toilet, slot parkir motor, area nongkrong, area music live, atm center. penambahan titik toilet, slot parkir motor, area meet up, area music live, atm center. Berdasarkan fakta lapang di atas, penulis ingin melakukan penelitian lebih dalam mengenai Mengetahui upaya manajemen dalam mengelola tenant dan fasilitas.